Non-diaphragm electrodeposition of antimony: Effect of process parameters and precipitating agents - Morcali M.H.; Küçükoğlu Ö.; Çetiner B.N.; Aktaş S. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2022)
Metallic antimony production from antimony-bearing materials is a research hotspot. The conventional electrowinning technology of antimony is a challenging problem due to the sulfur compounds that come from both the ore itself and the leaching solution in the electrolysis system. The electro-production of antimony in modified non-diaphragm cells is of interest because of the high price and maintenance issues associated with diaphragm cells. A sulfur-based problem in non-diaphragm cells was the focus of this study, which investigated the effects of various salts on this problem and also optimized antimony production conditions. Various salts (i.e., BaCl2, CaCl2, Ba(OH)2, Ca(OH)2) were used as a precipitating agent for the formation of insoluble salts (BaSO4/CaSO4 and BaSO3/CaSO3). Sb concentration, amount of NaOH and Na2S in the bath, electrowinning time, and temperature were investigated to optimize reaction parameters. The Taguchi experimental design was used to determine the effect of each factor on the Sb deposition. The phases and structures formed during electroproduction were identified with the help of various measurement techniques. This study found that in the presence of 96 mM BaCl2, 45 g/L of Sb concentration, 100 g/L of NaOH, and 60 g/L of Na2S were the most suitable factors. It was found that 40 oC was the optimal electrowinning temperature. This result also demonstrated that increasing concentrations of BaCl2 reduced specific energy consumption.